The Effect of Modifications To Traditional Games On Football Passing Results Among Extracurricular Students At SMAN 1 Blega (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the effect of modifying traditional games on the passing results in football among extracurricular students at SMAN 1 Blega. The method used is a quasi-experimental design with a one-group pre-test post-test approach, involving 20 students as the sample. The treatment provided consists of training using the El Rondo model, which is a modification of the traditional game of tag. Data were collected through short passing tests before and after the treatment. The analysis results show that the significance value (sig.) from the paired sample T-test is 0.000, which is less than 0.05, indicating a significant difference between the pretest and posttest results. Therefore, it can be concluded that the modification of traditional games has a positive effect on improving the passing accuracy of football students. This research is expected to contribute to the development of more effective training methods to enhance basic football skills, particularly passing, among students.